Understanding thermoforming - Throne, James L., 1937- (Cincinnati (Ohio) : Hanser Gardner Publications, 2008)
Modern thermoforming practice is a balance of practical experience and the application of engineering principles. This very practical book introduces the process, its tools and machinery, and the commonly used materials to novices and practicing engineers alike.
Includes bibliographical references (p. [243]-248) and index.
Keywords: Thermoforming; Thermoplastics